Comprehensive Chlorine Suppression: Advances in Materials and System Technologies for Direct Seawater Electrolysis - Zhao, Cenkai; Ding, Zheyuan; Zhang, Kunye; Du, Ziting; Fang, Haiqiu; Chen, Ling; Jiang, Hao; Wang, Min; Wu, Mingbo (Nano-Micro Letters, 2025)
Seawater electrolysis offers a promising pathway to generate green hydrogen, which is crucial for the net-zero emission targets. Indirect seawater electrolysis is severely limited by high energy demands and system complexity, while the direct seawater electrolysis bypasses pre-treatment, offering a simpler and more cost-effective solution. However, the chlorine evolution reaction and impurities in the seawater lead to severe corrosion and hinder electrolysis’s efficiency. Herein, we review recent advances in the rational design of chlorine-suppressive catalysts and integrated electrolysis systems architectures for chloride-induced corrosion, with simultaneous enhancement of Faradaic efficiency and reduction of electrolysis’s cost. Furthermore, promising directions are proposed for durable and efficient seawater electrolysis systems. This review provides perspectives for seawater electrolysis toward sustainable energy conversion and environmental protection. Highlights: 1 Rational design of chlorine-suppressing catalysts based on mechanistic insights. 2 Overview of recent advances in cutting-edge seawater electrolysis systems. 3 Discussion of challenges and potential directions for direct seawater electrolysis enhancement.